Intra-Extramusical Resonance of Western Pop Songs on Indonesians in a Communication Perspective - Pandu Watu Alam; Riyan Hidayatullah (Cinematology: Journal Anthology of Film and Television Studies, 2022)
The song is music with lyrics, one of the aesthetic communication media that can convey one's ideas or thoughts. The message conveyed by a song does not only rely on intramusical factors but also extramusical factors that influence listeners in understanding a piece of work, especially with lyrics in foreign (Western) languages. This research aims to find out how the transmission of Western songs in Indonesia is from a communication perspective? What intra and extra-musical factors do Indonesians absorb in Western songs? What is the form of musical communication of Western songs in the context of Indonesian society? Qualitative methods are used in this study so that the results obtained can be described in the form of narration and illustrative chart images. From the results of the study, listeners to western pop songs in Indonesia initially tended to think that songs in foreign languages (English) were superior and even had a special place in the listeners' hearts. However, along with technological developments and all the conveniences they have, the intra-extramusical resonance of western pop songs is increasingly varied, no longer just following the trend of becoming fans of western pop songs, many Indonesian people also become creators and combine it with Indonesian traditional music or with other cultures. another (fusion). The intra-extramusical factor which is an element of musical communication that occurs in western pop songs in Indonesia seems to have been the reason for how effectively musical communication is used to convey messages, whether it is used in the world of basic education, health therapy, or intercultural communication (west and east). as a place for cultural acculturation. The progress of the times and the role of the media are inseparable from the massive resonance of the spread of western pop songs through digital platforms such as spotify, youtube, and others. So now connoisseurs of we